The Zakah Recipients Satisfactory Among Low Level Income Society in Yogyakarta - Zein Muttaqin; Hasan Al Banna (Share: Jurnal Ekonomi dan Keuangan Islam, 2015)
Since its emergence in the last decade, zakah has become a new hope to the low level income society to improve their opportunity to breakthrough the poverty line. However, the potential of zakah to eradicate the poverty is yet to be achieved, it happens due to three reasons, they are (1) the proportion of zakah fund that has been distributed into the economy sectors has not become a major program; (2) the regulation regarding zakat still hanging; (3) the consumptive behavior still become the driving factors in the society. This paper is attempted to measure mustahiqs’ satisfaction over zakah distribution, which is affecting they opportunities to improve their living standard. By presenting the data in form of field research and using regression found that the service quality, mentoring is influencing the satisfaction of mustahiqs. ABSTRAK - Perkembangan zakat dalam dekade terakhir ini menjadikannya sebagai sebuah harapan baru bagi masyarakat berpendapatan rendah untuk meningkatkan kesempatannya untuk keluar dari garis kemiskinan. Namun, potensi zakat dalam mengurangi kemiskinan masih belum dapat dicapai, hal ini terjadi karena tiga alasan, (1) proporsi dana zakat yang didistribusikan kepada sektor- sektor ekonomi bukanlah menjadi program utama; (2) Aturan yang berkaitan dengan zakat masih belum berjalan dengan baik; (3) Perilaku konsumtif masih menjadi faktor yang berpengaruh di dalam masyarakat. Penelitian ini bertujuan untuk mengukur kepuasan mustahiq melalui distribusi zakat yang dapat mempengaruhi kesempatan guna meningkatkan standar hidup mereka. Dengan memaparkan data dalam bentuk riset lapangan dan menggunakan regresi maka ditemukan bahwa kualitas pelayanan, mentoring dapat mempengaruhi kepuasan mustahiq.